(untitled) (Damascus University Journal for legal sciences, 2025)
Most of the legislation regulating the provisions of compulsory execution tends towards adopting a set of legal mechanisms aimed at softening and simplifying the strictness of compulsory execution procedures, The idea of amicable sale of seized funds is considered one of the most prominent legal mechanisms enshrined in some contemporary legislations, within certain procedural controls and conditions, and within the limits that serve the purposes of compulsory execution, with a focus on achieving the desired balance between the interest of the seizing creditor in obtaining his right through quick and easy procedures and with simple expenses, and the interest of the debtor with seizure in ensuring a minimum From the legal protection of his privacy and his personal and financial entity, and this appears by giving him the opportunity to access the actual value of his seized funds, so that he can cover all of his debts, or at least pay off the largest possible amount of them, in a way that ultimately guarantees the effectiveness of forced enforcement procedures.